Safe decommissioning for Nuclear activities - International Conference on Safe Decommissioning for Nuclearr Activi ties, (2002 : Berlin, Germany); International Atomic Energy Agency (Vienna : International Atomic Ennergy Agency, 2003)
This companion CD has been prepared from the original material as su bmitted by the authors. The views expressed do not necessarily reflect those of the IAEA, the governments of the nominating Member States or the nominating organizations.
This conference was organized by the International Atomic Energy Age ncy and hosted by the Government of Germany through the Bundesamt fur S trahlenschutz.
The conference was held in Berlin from 14-18 October 2002.
Keywords: Nuclear power plants -- Decommissioning; Nuclear facilities -- Decommissioning